The fulfillment of promises, obligatory or recommended?(mostahab)? - ÃšÂ©Ã™Â„Ã˜Â§Ã™Â†Ã˜ÂªÃ˜Â±Ã›ÂŒ, Ã˜Â¹Ã™Â„Ã›ÂŒ Ã˜Â§ÃšÂ©Ã˜Â¨Ã˜Â± (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
In the popular view, the fulfillment of promises is recommended, apparently its reason being, in addition to consensus, some traditions. However, all of these reasons appear to be distorted and unreliable. On the contrary, we find a lot of traditions and evidence which entail the necessity to fulfill promises.